Prosodic Analysis of English Utterances in Student with Attention Deficit Hyperactivity Disorder in the Context of Riddle Game - Amal, Rizal Alamsa; Hariri, Tatang (Pascasarjana Universitas Negeri Makassar, 2025)
This study focuses on prosodic patterns, specifically intonation and stress, in student with attention deficit hyperactivity disorder (ADHD) during riddle game situations. The main objective of this research is to identify and analyze how ADHD and other factors influence prosodic patterns in English speech as a second language in a gaming context. The data source comes from an 11-year-old ADHD student with the initials D, who studies at Corner Stone School in Makassar. Data collection was conducted using an observation technique. Observations were carried out while playing a riddle game, with audio recordings used for analysis. The results indicate a tendency to emphasize the beginning of utterances, such as the words